First Multipurpose Task Specific Ionic Liquid: Designing and Synthesis of Novel Dimethyl Formamide-Like Ionic Liquid and Its Applications as a Green Solvent Alternative to Dimethyl Formamide Dependent Reactions - Ali Hullio, Ahmed; Mastoi, G.M.; M. Khan, Khalid (Asian Journal of Chemistry, 2011)
A novel imidazole based task specific ionic liquid with dimethyl formamide (DMF) functionality has been designed and synthesized. The proposed dimethyl formamide like task specific can be used as a green alternative solvent-cum-organocatalyst for wide range of organic reactions which essentially depend on DMF. Dimethyl formamide as a solvent, due to its inherited structural features is found to affect the outcome of many reactions. Some of DMF-dependent reactions are investigated in its ionic liquid version with encouraging results. DMF-like ionic liquid acts both as a green reaction media and recyclable organocatalyst. Main advantages include easy reaction procedure, short reaction duration, easy work up and moreover the wide scope applications.